An autopsy based descriptive study of the spectrum of pulmonary lesions encountered in fetal deaths at a tertiary care center - Saara Neeha; Santosh Rao Kattimani; Anita A Mahanta; Anuradha G Patil (Wolters Kluwer Medknow Publications, 2018)
Background: Fetal autopsy has been an indispensable tool in evaluating the cause of death. The most common cause for fetal deaths is associated with respiratory disorders accounting for around 60%. This study was undertaken to evaluate the gross and microscopic features of lungs in fetal autopsies and estimate the incidence of deaths attributable to pulmonary causes. Materials and Methods: All fetuses received for autopsy at our institute were included in the study with prior consent. Gross and microscopic findings along with relevant clinical data were recorded. Results: A total of 426 autopsies were conducted from January 2011 to August 2016. Of those, 184 had abnormal pulmonary findings constituting 43.19%. Aspiration pneumonia was the most common finding with 67 cases (36.4%), followed by atelectasis 54 cases (29.3%), congenital cystic adenomatoid malformation in 13 cases (7.1%), lung hypoplasia 12 cases (6.5%), pulmonary hemorrhage 21 (11.4%), 15 cases (8.15%) of hyaline membrane disease, one case (0.5%) of heterotaxy, and one case of extralobar pulmonary sequestration (0.5%). Congenital malformations of lungs were seen in 27 (14.67%) cases and 38 cases (20.65%) had other associated anomalies. Conclusion: Pulmonary pathology is the most common finding in fetal deaths with aspiration pneumonitis being the most common avoidable cause. Accurate fetal autopsy along with clinical data are important in evaluating fetal deaths and can help in reduction of unexplained stillbirths.